Review of Postpartum Depression Risk Factors and Treatment in India (International Journal of Food and Nutritional Sciences, 2022)
Depression that predominates in the postpartum period is known as postpartum depression, and it is more common in research and clinical practise up to a year after birth. Other signs of postpartum depression in women include mood swings or lability and excessive worry for the newborn. In addition, anxiety disorders or severe anxiety symptoms are frequently linked to postpartum depression. Postpartum depression is more likely to affect women who have had a history of mental illness. A serious psychiatric condition called postpartum depression causes a great deal of handicap in women and is frequently linked to serious risks for children's emotional, behavioural, and cognitive development. This condition is frequently undiagnosed and undertreated. Because it affects a woman's ability to care for herself and her children, postpartum depression is an important issue that has to be addressed. It has an impact on a child's mental development as well. For these reasons, it is necessary to evaluate risk factors in order to fully understand all aspects of postpartum depression in women. In this article, postpartum depression in India is discussed along with its risk factors and treatment options. Women have traditionally been grouped in traditional studies for postpartum depression risk factors into a certain pregnancy stage that precedes postpartum depression.